Fragile X Syndrome and Targeted Treatments - Nattaporn Tassanakijpanich; Ana María Cabal-Herrera; Maria Jimena Salcedo-Arellano; Randi Jenssen Hagerman (Faculty of Medicine, Diponegoro University, 2020)
Many targeted treatment studies have been carried out in individuals with Fragile X Syndrome (FXS) guided by animal studies from the Fragile X Mental Retardation 1 (FMR1) knock out (KO) mice and the fragile X Drosophila studies. Here we review the many medications that have been studied in patients with FXS and some of these medications are available for clinical use by wise clinicians. Other medications are not currently available by prescription because they are not approved by the FDA. No medication has received specific approval for treatment of FXS, although some have shown benefit from clinical studies. There is much to be done in the treatment of those with FXS and this report describes those pharmacological treatments that target the neurobiological mechanisms that are dysregulated by the lack of the Fragile X Protein (FMRP) in those with FXS.